Continuous Midwifery Care Ensures Safe Maternal and Neonatal Outcomes: Asuhan Kebidanan Berkesinambungan Memastikan Hasil yang Aman bagi Ibu dan Bayi Baru Lahir - Akhmalia, Nela; Azizah, Nurul (Universitas Muhammadiyah Sidoarjo, 2025)
Midwives try to reduce MMR by providing continuous midwifery care (CoC) for pregnant women to postpartum women. Continued care (COC) is midwifery care with a continuous service model for women during pregnancy to postpartum and family planning. The purpose of this study was to analyze midwifery care using the continuous care method in the independent practice of midwives. The design of this case study research uses a descriptive method, where Mrs. M was given midwifery care starting from the third trimester of pregnancy, childbirth, newborns, postpartum to family planning. Continuous midwifery care (CoC) for Mrs. M is standard midwifery care. The results of the study showed that after providing midwifery care to Mrs. M, it was found that the condition of the mother and baby was healthy or within normal limits, there were no complications until the implementation of care was completed. During the postpartum period, Kegel exercises were performed because Mrs. M was afraid that her vagina would not return to normal because heaching was not performed. Conclusion: Continuous midwifery care provided to the subject was in accordance with the applicable midwifery service standards. Highlights: Comprehensive Care: Midwifery services covered pregnancy to family planning. Positive Outcomes: Mother and baby remained healthy without complications. Standard Compliance: Care followed established midwifery service standards. Keywords: Continue of Care, Midwifery, Service